On toleration - Walzer, Michael (New Haven : Yale University Press, 1997)
Michael Walzer examines five "regimes of toleration"--Multinational empires to immigrant societies - and describes the strengths and weaknesses of each regime, as well as the varying forms of toleration and exclusion each fosters. Walzer shows how power, class, and gender interact with religion, race, and ethnicity in the different regimes and discusses how toleration works - and how it should work - in multicultural societies like the United States. Walzer offers an eloquent defense of toleration, group differences, and pluralism, moving quickly from theory to practical issues, concrete examples, and hard questions. His concluding argument is focused on the contemporary United States and represents an effort to join and advance the debates about "culture war," the "politics of difference," and the "disuniting of America." Although he takes a grim view of contemporary politics, he is optimistic about the possibility of coexistence: cultural pluralism and a common citizenship can go together, he suggests, in a strong and egalitarian democracy
Introduction. How to write about toleration -- Personal attitudes and political arrangements -- Five regimes of toleration -- Complicated cases -- Practical issues -- Modern and postmodern toleration -- Epilogue. Reflections on American multiculturalism.
Includes bibliographical references (pages 113-119) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Human rights; Toleration; Cultural pluralism; Multiculturalism; Human Rights; Cultural Diversity; Droits économiques et sociaux; Tolérance.; Diversité culturelle; Multiculturalisme; Droits de l'homme (Droit international); multiculturalism; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Pluralisme culturel; Minorités ethniques; Liberté religieuse; Relations raciales; Etats-Unis d'Amérique.; Europe; Cultural pluralism; Human rights; Multiculturalism; Toleration; Verdraagzaamheid; Plurale samenleving; Multiculturele samenlevingen; Droits de l'homme.; Multiculturalisme; Tolérance.; Pluralisme (sciences sociales)